Effectiveness of text message based, diabetes self management support programme (SMS4BG): two arm, parallel randomised controlled trial. (17th May 2018) - Dobson, Rosie; Whittaker, Robyn; Jiang, Yannan; Maddison, Ralph; Shepherd, Matthew; McNamara, Catherine; Cutfield, Richard; Khanolkar, Manish; Murphy, Rinki
Abstract: Objective: To determine the effectiveness of a theoretically based and individually tailored, text message based, diabetes self management support intervention (SMS4BG) in adults with poorly controlled diabetes. Design: Nine month, two arm, parallel randomised controlled trial. Setting: Primary and secondary healthcare services in New Zealand. Participants: 366 participants aged 16 years and over with poorly controlled type 1 or type 2 diabetes (HbA1c ≥65 mmol/mol or 8%) randomised between June 2015 and November 2016 (n=183 intervention, n=183 control). Interventions: The intervention group received a tailored package of text messages for up to nine months in addition to usual care. Text messages provided information, support, motivation, and reminders related to diabetes self management and lifestyle behaviours. The control group received usual care. Messages were delivered by a specifically designed automated content management system. Main outcome measures: Primary outcome measure was change in glycaemic control (HbA1c) from baseline to nine months. Secondary outcomes included change in HbA1c at three and six months, and self efficacy, diabetes self care behaviours, diabetes distress, perceptions and beliefs about diabetes, health related quality of life, perceived support for diabetes management, and intervention engagement and satisfaction at nine months. Regression models adjusted for baseline outcome, health district category, diabetes type, and ethnicity. Results: The reduction in HbA1c at nine months was significantly greater in the intervention group (mean −8.85 mmol/mol (standard deviation 14.84)) than in the control group (−3.96 mmol/mol (17.02); adjusted mean difference −4.23 (95% confidence interval −7.30 to −1.15), P=0.007). Of 21 secondary outcomes, only four showed statistically significant improvements in favour of the intervention group at nine months. Significant improvements were seen for foot care behaviour (adjusted mean difference 0.85 (95% confidence interval 0.40 to 1.29), P<0.001), overall diabetes support (0.26 (0.03 to 0.50), P=0.03), health status on the EQ-5D visual analogue scale (4.38 (0.44 to 8.33), P=0.03), and perceptions of illness identity (−0.54 (−1.04 to −0.03), P=0.04). High levels of satisfaction with SMS4BG were found, with 161 (95%) of 169 participants reporting it to be useful, and 164 (97%) willing to recommend the programme to other people with diabetes. Conclusion: A tailored, text message based, self management support programme resulted in modest improvements in glycaemic control in adults with poorly controlled diabetes. Although the clinical significance of these results is unclear, the findings support further investigation into the use of SMS4BG and other text message based support for this patient population. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12614001232628.